Treatment strategies for Sjögren's syndrome with childhood onset: a systematic review of the literature. (21st July 2021) - Doolan, Georgia; Faizal, Nor Mohd; Foley, Charlene; Al-Obaidi, Muthana; Jury, Elizabeth C; Price, Elizabeth; Ramanan, Athimalaipet V; Lieberman, Scott M; Ciurtin, Coziana
Abstract: Objectives: SS with childhood onset is a rare autoimmune disease characterized by heterogeneous presentation. The lack of validated classification criteria makes it challenging to diagnose. Evidence-based guidelines for treatment of juvenile SS are not available due to the rarity of disease and the paucity of research in this patient population. This systematic review aims to summarize and appraise the current literature focused on pharmacological strategies for management of SS with childhood onset. Methods: PubMed and MEDLINE/Scopus databases up to December 2020 were screened for suitable reports highlighting pharmacological treatment of SS with childhood onset using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2009 reporting checklist. Animal studies were excluded. Results: A total of 43 studies (34 case reports, 8 mini case series and 1 pilot study) were eligible for analysis. The studies retrieved included girls in 88% (120/137) of cases and had very low confidence levels. HCQ was prescribed for parotid swelling, as well as in association with MTX and NSAIDs in patients with arthritis and arthralgia. Corticosteroids such as long courses of oral prednisone and i.v. methylprednisolone were commonly prescribed for children with severe disease presentations. Rituximab was mainly indicated for mucosa-associated lymphoid tissue lymphoma and renal and nervous system complications. Other conventional DMARDs were prescribed in selected cases with extraglandular manifestations. Conclusion: Various therapies are used for the management of juvenile SS and are prescribed based on expert clinician's opinion. There are currently no good-quality studies that allow clinical recommendations for treatment of SS with childhood onset.